Strategy for the Development of Electronic Journal Collections (E-Journals) at the Muhammadiyah University of North Sumatra (UMSU) Library - Nurainun Syahfitri (International Journal of Cultural and Social Science, 2022)
This study aims to determine the strategy for developing e-journal collections at the University of Muhammadiyah Sumatra Utara (UMSU) Library and the role of librarians in developing e-journal collections. This type of research is descriptive research using a qualitative approach. The technique of collecting data in this research is through observation, interviews, and documentation. The data analysis technique of this research uses data reduction, data presentation and conclusion drawing. The results of the study show that the strategy for developing e-journal collections is by coordinating with all academic study programs, collaborating with the National Library through e-resources, collaborating with FPPTMA (Muhammadiyah Aisyiyyah College Library Forum) as well as library socialization on the use of e-journal collections. . Constraints faced in developing the e-journal collection are: budget/funds, HR (Human Resources) and users. The role of the librarian in developing e-journal collections is to provide knowledge on how to access or browse information, promote e-journals through brochures, pamphlets, social media or web news at the UMSU Library and conduct socialization to the entire UMSU campus academic community.